The '85 Bears : we were the greatest--25th anniversary - Ditka, Mike. frey50; Telander, Rick. (Chicago : Triumph Books, 2010)
A must-have for Bears fans, this is the ultimate record of a great franchise's greatest season as told by none other than Da Coach himself.
Introduction -- Where are the trucks? -- We'll be back! -- Rope burns -- No saints here -- Bodyslams and all-day suckers -- A dog on my ankle -- Yolanda is waiting, Meester Deetka -- Sic 'em Fridge, and the premature celebration -- Hit lists in Cheeseland, the marvelous mudslide, halfway home -- Howling sounds and defenders from another planet -- Traveling south, near-blows with Buddy, Monday Night hell -- We can do almost everything, but maybe we can't dance -- Headband craziness, a Yuppie who likes to hurt people, the elephant in the snow -- Cannons don't fall out of trees -- Stick a needle in this -- Afterword.
Includes a bonus audio Compact disc featuring an exclusive interview with Mike Ditka that provides even more memories from the truly golden era of Chicago football.
The game summaries, "Remembering '85" interviews, and statistical appendices appeared previously in "The '85 Bears: still Chicago's team", c2005. Portions of the main narrative text appeared previously in the book "In life, first you kick ass", c2005 by Mike Ditka and Rick Telander.
Keywords: Ditka, Mike; Chicago Bears (Football team); Football teams -- Illinois -- Chicago